Muito mais do que incentivos fiscais: A(s) história(s), a(s) política(s), e o desenvolvimento local em Montes Claros/MG - Felipe Fróes Couto (2015)
Due to constant failures of development policies in the region, the North of Minas Gerais State has increasingly demanded the attention of the Federal and State spheres of Government. The municipalities are in a weaker position compared to other federal entities and have claimed resources to the region, especially with respect to federal investment programs, as the main and most effective way to bring progress to local realities. The present research aims, from a theoretical parallel to be drawn between the notions of local development and regional development policies by tax incentives, to promote an analysis of fiscal incentive policies as a factor of development in the case of Montes Claros, North of Minas Gerais, municipality characterized by incentives granted mainly by the Federal and Local Government. There is, over the course of this research, important emphasis on the role of Municipal Government as a central point of interest and key element of development conditions promotion in that context. The framework of analysis of local development experience Montes Claros-MG was made from the comparison of empirical data with three main dimensions. The first relates to the unique attributes of the place, its historical, cultural factors, geographical and economical factors. The second relates to local political dynamics and public policy planning for local development. Finally, the third are the meanings and effects of fiscal incentives for policy relevant social actors. To analyze the role of tax incentives policy in local development, as proposed, it was important to analyze the purpose of fiscal incentive policies, the local political scene and the local planning of such policies, the governmental control in relation to the incentives objectives and to identify their effects with respect to externalities. It was concluded that there is great difficulty in planning public policies in Brazil, mainly in the municipal sphere, and that the policies of fiscal incentives do not contribute directly to local development in the case reviewed because they are not part of a political project of local development that considers local economic potential.